Some aspects of digitalization in the methodological and mathematical training of future primary school teachers - Nafiset Muratovna Evtykhova; Lyubov Leonidovna Burkova (Вестник Майкопского государственного технологического университета)
The relevance. The need for distance learning during the pandemic and mixed learning has now led to an accelerated study of using various digital resources. Digital transformation has become a part of the educational process. This is evidenced by such documents as Decree of the President of the Russian Federation of July 21, 2020 No. 474 "On the National Development Goals of the Russian Federation for the period up to 2030", which lists the achievement of "digital maturity" of key sectors of the economy and the social sphere as one of the target indicators of the national goal of "digital transformation". As well as by the "Strategy for the Digital Transformation of Science and Higher Education" and the "Passport of the Strategy of "Digital Transformation of Education", published on the websites of the Ministry of Education and Science and the Ministry of Education of the Russian Federation. Mathematical training of future primary school teachers, as well as comprehensive training, is becoming one of the most important tasks of education.The problem of the research is to identify the most effective digital resources and methods of their application in the context of blended teaching Mathematics to future primary school teachers.The purpose of the article is to reflect some aspects that one has to face in the real educational process during the mathematical training of future primary school teachers in the context of the digital transformation of education.The research methods used are analysis of sources and literature on the research topic, observation, generalization of the experience of using digital resources in educational activities.The research results and conclusions are as follows, the authors have analyzed and summarized regulatory documents; the use of digital resources in teaching mathematics has been investigated; an option of the use of digital resources presented. The study has showed the need to develop teaching aids on the use of digital resources in the process of mathematical and methodological training of future primary school teachers.